2022
DOI: 10.33411/ijist/2021030511
|View full text |Cite
|
Sign up to set email alerts
|

Compact Frequency Selective Surface (FSS) for X-Band Shielding

Abstract: With the increase in the usage of electromagnetic devices, electromagnetic interference increased many folds. Frequency Selective Surface (FSS) provide effective shielding from unwanted frequency ranges. A thin, conformal band-stop FSS is presented in this research that provides effective electromagnetic shielding properties in X-band. The FSS acts as a band stop filter at 10 GHz. The proposed FSS has 54.7% fractional bandwidth. The design is of the dimensions 6.79 x 6.79 x 0.127 milimeter cube, employing Rog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The proposed FSS unit cell is 83% smaller than the double‐sided solution in Zouaoui et al 13 The proposed FSS offers good attenuation characteristics and the realized rejection bandwidth is 40% calculated at |S 21 | ≤ −15 dB. The realized bandwidth is greater than the research works reported in other studies 8–17 . The rejection bandwidth is 48% for Nauman et al 9 calculated with |S 21 | ≤ −3 dB.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…The proposed FSS unit cell is 83% smaller than the double‐sided solution in Zouaoui et al 13 The proposed FSS offers good attenuation characteristics and the realized rejection bandwidth is 40% calculated at |S 21 | ≤ −15 dB. The realized bandwidth is greater than the research works reported in other studies 8–17 . The rejection bandwidth is 48% for Nauman et al 9 calculated with |S 21 | ≤ −3 dB.…”
Section: Resultsmentioning
confidence: 66%
“…13,18 2. The proposed FSS has higher flexibility compared to those in other studies, [8][9][10][11][12][13][14][15][16][17] and the profile thickness is at least 52% thinner than the solutions presented in the literature. 3.…”
Section: Fabrication and Measurementmentioning
confidence: 77%
See 3 more Smart Citations